2006
DOI: 10.1001/archotol.132.2.206
|View full text |Cite
|
Sign up to set email alerts
|

Hypopharyngeal Surgery in Obstructive Sleep Apnea

Abstract: To perform an evidence-based medicine review of the literature describing outcomes of hypopharyngeal surgery in obstructive sleep apnea. Design: We performed a MEDLINE search of Englishlanguage articles or abstracts using the keywords sleep and surgery in combination with any of the following terms: hypopharynx, tongue, tongue base, epiglottis, genioglossus, advancement, mortised, genioplasty, glossectomy, tongue radiofrequency, hyoepiglottoplasty, hyoid, suspension, and stabilization. Additional studies were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
162
2
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 210 publications
(179 citation statements)
references
References 44 publications
6
162
2
2
Order By: Relevance
“…An evidence-based medicine review included 36 articles, mainly case series with level 4 evidence [1]. The review showed success rates between 17 and 83% of the various procedures.…”
Section: Introductionmentioning
confidence: 99%
“…An evidence-based medicine review included 36 articles, mainly case series with level 4 evidence [1]. The review showed success rates between 17 and 83% of the various procedures.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the efficacy of these procedures was found to be poor when assessed using clinically important endpoints. The success of surgery has historically been reported in terms of ≥50% reduction in AHI score from baseline or to a score of ≤20 102. It appears questionable to declare surgery as successful if moderate OSA (an AHI score of 16-30) 1 persists in postoperative patients.…”
mentioning
confidence: 99%
“…Severe mandibular retrognathism is often accompanied by pharyngeal airway obstruction,3 probably because of downward displacement of the tongue. Therefore, advancement genioplasty can achieve extensive anterior retraction of the suprahyoid musculature and decrease the signs and symptoms of obstructive sleep apnea syndrome, including the apnea–hypopnea index 1617. Moreover, the posterior airway space significantly increases after advancement genioplasty 1819.…”
Section: Discussionmentioning
confidence: 99%